Neo-nervegenesis in 3D dynamic responsive implant for inguinal hernia repair. Qualitative study. (April 2020) - Amato, Giuseppe; Agrusa, Antonino; Puleio, Roberto; Calò, Piergiorgio; Goetze, Thorsten; Romano, Giorgio
Abstract: Background: Prosthetic repair of inguinal hernias is one of the most performed surgical procedures. Nevertheless, high rates of complications affect the surgical treatment. Implant fixation, poor-quality tissue ingrowth and mesh shrinkage seem to be involved in postoperative complications, discomfort and chronic pain following inguinal hernia repair. To address these issues a multilamellar shaped 3D dynamic responsive prosthesis has been developed. This new implant, positioned fixation-free to obliterate the hernia opening, thanks its inherent dynamic compliance during inguinal movements, has demonstrated to induce an enhanced biological response. The ingrowth of newly formed muscle fibers, arteries and veins in a surrounding of viable connective tissue could be evidenced into the implant fabric. This appears to be quite different from the fibrotic plaque, typical biologic response of conventional meshes. In addition to myocytes and vessels, newly ingrown nerves have also been detected in the prosthetic structure. Materials and methods: The aim of this investigation was to determine by examining biopsy specimens excised from patients who underwent hernia repair with the 3D dynamic implant, quantity and quality of the neural ingrowth within the implant fabric in the short, medium, and long term post-implantation. Results: Newly formed nervous structures were found in biopsy specimens, from multiple spots of nerve clusters evidenced in the short-term along the increased level of neural maturation in the midterm, until the nerves showed complete in all components in the long-term. Conclusion: The development of highly specialized nervous tissue in the 3D prosthesis seems to finalize the regenerative biologic response that is expected for the treatment of a degenerative disease, as, in fact, inguinal hernia is. Re-growth of the typical tissue components of the groin evidenced in the 3D dynamic prosthesis seems to effectively revert the degenerative source of inguinal hernia into regeneration of the vanished tissue components of the groin. Highlights: Evidencing enhanced biological response in 3D prosthesis for inguinal hernia repair. Ingrowth of newly formed nervous structures histologically verified into the prosthesis. Neonervegenesis within the implant fabric as a result of dynamic responsivity. The development and maturation of highly specialized tissue finalizes the regenerative response induced by the 3D prosthesis. Regenerative biologic response is pathogenetically coherent for the cure of a degenerative disease like inguinal hernia.